Therapeutic Effects of BT2 in the Hippocampus of Alzheimer's Disease Mouse Model. (14th June 2022) - Mullins, Caitlyn; Mohankumar, Puliyur Seshadri; Reddy, Hemachandra; Shah, Harsh; Shin, Andrew; Siddik, Bakkar
Abstract: Objectives: Alzheimer's disease (AD) is the most common type of dementia affecting more than 6 million Americans today. Despite the increasing rates of AD there is still no effective cure for this devastating disease. Our lab has shown that elevated plasma branched-chain amino acids (BCAAs) and their metabolites are present in both AD patients and mice. Further pilot data revealed that 8 weeks of dietary BCAA restriction in AD mice alleviated AD-related brain pathology and improved cognitive function. Although we observed beneficial effects from the dietary intervention, this approach is practically challenging because BCAAs are found in a wide variety of foods. This prompted us to test the effects of lowering plasma BCAAs in AD mice pharmacologically by BT2, a small molecule that increases BCAA breakdown. Methods: We used cognitively intact, 2-month-old 5xFAD mice or wildtype (WT) mice to test the effects of BT2 on early AD-related brain pathology. Animals were injected with BT2 or vehicle intraperitoneally (60 mg/kg) for 30 consecutive days. Brain micro punches were taken from the hippocampus for monoamine analysis, and the rest of the hippocampal tissues were used for gene analysis via RT-qPCR. Next, we treated cognitively impaired 4-month-old 5xFAD mice and WT mice with either BT2 (60 mg/kg) or vehicle for 10 consecutive days. We used Golgi-Cox staining to visualize the hippocampus. Results: BT2 treatment in 2-month-old 5xFAD mice restored key neurotransmitters in the hippocampus, the main brain region responsible for learning and memory. BT2 also reduced mRNAs involved in ER stress, inflammation, and Aβ-42 production. Next, we sought to determine if the changes in brain pathology and neurotransmitter status induced by BT2 would result in restored neuronal morphology in the hippocampus of cognitively impaired 5xFAD mice. We observed a clear restoration in dendritic density in the hippocampus of 5xFAD mice treated with BT2 compared to WTs. We did not observe any changes in cognitive function in these mice, possibly due to the short treatment duration. Conclusions: Our findings suggest that BT2 has therapeutic effects on AD-related pathology in the hippocampus of 5xFAD mice, indicating the potential of BT2 as a novel preventive/treatment strategy for AD. Funding Sources: NIH R21 AG069140-01